Multimod Mark III : The Core Dynamic and Steady State Model - Faruqee, Hamid; Isard, Peter; Laxton, Douglas; Turtelboom, Bart. (Washington, D.C. : International Monetary Fund, 1998)
This study describes the Mark III version of MULTIMOD, the IMF's multi region macroeconomic model. Mark III version of MULTIMOD differs from its predecessor in several important respects. New features include a core steady-state analogue model, a new model of teh inflation-unemployment nexus, and extended non-Ricardian specification of consumption-saving behavior, and improved specifications and estimates of investment behavior and international trade equations. In addition, the introduction of a new solution algorithm has greatly increased the robustness, speed of convergence, and accuracy of the simulations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet